HUBUNGAN KEMAMPUAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BLORA - Silvi Nur Ariskha; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The change of life and the quality of human resources that are currently increasing will affect the development of society. This change can encourage the improvement of the performance of employees at Government agencies to give good service. There are two factors that affect employee performance which are work motivation and skill. There are employees who have worked according to the standard so that the work is done on time, but there are also employees whose work does not reach the target. This study aims to determine the relationship between the work motivation and skill towards the performance of employees of the Department of Population and Civil Registration of Blora Regency. This study uses an associative quantitative method involving 40 employees as respondents drawn from 64 employees. The result of Kendall Tau rank correlation coefficient of skill or ability with employee performance of 0.418 z count 3.8> z table 1.96 with the value of the KD of 17.5%, Kendall’s tau rank correlation coefficient of work motivation with employee performance 0.450 z count 4.090> z table 1.96 with the value of KD of 20.25%, Kendall concordance coefficient of 0.994, KD value of variable ability and work motivation simultaneously give effect to performance variable which is equal to 98.8%. The conclusion of this research is that there is correlation between ability and motivation of work with employee performance in Department of Population and Civil Registration of Blora Regency. The obstacles are the achievement of performance that is less than target and the inappropriate background of education. The suggestions given by researchers is providing training to improve the employee skills. The suggestions for further quantitative research are to add variables and for qualitative research that is by adding other factors of employee performance.